Arginase 1-Based Immune Modulatory Vaccines Induce Anticancer Immunity and Synergize with Anti-PD-1 Checkpoint Blockade - Aaboe Jørgensen, Mia; Ugel, Stefano; Linder Hübbe, Mie; Carretta, Marco; Perez-Penco, Maria; Weis-Banke, Stine Emilie; Martinenaite, Evelina; Kopp, Katharina; Chapellier, Marion; Adamo, Annalisa; De Sanctis, Francesco; Frusteri, Cristina; et al. (Cancer immunology research, 2021)
Expression of the L-arginine catabolizing enzyme arginase 1 (ARG1) is a central immunosuppressive mechanism mediated by tumor-educated myeloid cells. Increased activity of ARG1 promotes the formation of an immunosuppressive microenvironment and leads to a more aggressive phenotype in many cancers. Intrinsic T-cell immunity against ARG1-derived epitopes in the peripheral blood of cancer patients and healthy subjects has previously been demonstrated. To evaluate the antitumor efficacy of ARG1-derived peptide vaccines as a monotherapy and as a combinational therapy with checkpoint blockade, different syngeneic mouse tumor models were utilized. To evaluate the antitumor effects, flow cytometry analysis and IHC were performed on tumors, and ELISPOT assays were performed to characterize immune responses. We show that ARG1-targeting therapeutic vaccines were able to activate endogenous antitumor immunity in several syngeneic mouse tumor models and to modulate the cell composition of the tumor microenvironment without causing any associated side effects or systemic toxicity. ARG1-targeting vaccines in combination with anti-PD-1 also resulted in increased T-cell infiltration, decreased ARG1 expression, reduced suppressive function of tumor-educated myeloid cells, and a shift in the M1/M2 ratio of tumor-infiltrating macrophages. These results indicated that the induced shift toward a more proinflammatory microenvironment by ARG1-targeting immunotherapy favors effective tumor control when combined with anti-PD-1 checkpoint blockade. Our data illustrate the ability of ARG1-based immune modulatory vaccination to elicit antigen-specific immunosurveillance and imply the feasibility of this novel immunotherapeutic approach for clinical translation.